(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The article deals with one of the first “scandals” connected to the sexual sphere on Italian television, just out of its experimental period: the apparent nude (actually a pink leotard, hidden by the stage lights and the black and white) of dancer Alba Arnova in the variety show “La piazzetta” (1956). This story highlights the tension between the incident to be concealed and the need to discuss the rules of a newborn medium. More broadly, it underlines the dialogue between Italian traditional avanspettacolo, the model of “US-like” commercial television, the European public service ideal, and Catholic control.